Neisseria meningitidis Serogroup C Causing Primary Arthritis in a Child: Case Report. Issue 5 (February 2016) - Straticiuc, Sergiu; Ignat, Ancuta; Hanganu, Elena; Lupu, Vasile Valeriu; Ciubara, Alexandru Bogdan; Cretu, Roxana
Abstract : Abstract: Introduction: Neisseria meningitidis (N. meningitidis) is associated with severe invasive infections such as meningitis and fulminant septicemia. Septic arthritis due to N. meningitidis is rare and bone infections have been reported exceptionally. We report the case of a 1-year old girl who presented with a painful, swollen right knee, accompanied by fever and agitation. Arthrocentesis of the right knee, while patient was under anesthesia, yielded grossly purulent fluid, so we made arthrotomy and drainage. The culture from synovial fluid revealed N. meningitidis, sensitive to Ceftriaxone. The patient received intravenous antibiotherapy with Ceftriaxone. The status of the patient improved after surgical drainage and intravenous antibiotic therapy. She recovered completely after 1 month. Conclusion: This observation illustrates an unusual presentation of invasive meningococcal infection and the early identification of the bacteria, combined with the correct treatment, prevent the complications and even death.